Seeking empathy: mediators for an automated administration - Oscar Expósito-López (International Journal of Digital Law)
Technological advancements in the field of artificial intelligence are increasingly bringing us closer to the possibility of incorporating automation in administrative decision-making. This tool would yield significant benefits in key areas such as efficiency and improvement of public services. However, it also poses risks, such as the potential loss of empathy that public workers contribute to decision-making and even the displacement of administrative personnel engaged in the processing of files. This study aims to delve into the aspects where the implementation of automated administration would be feasible, distinguishing between rule-based and discretionary decisions. Administrative mediation and artificial intelligence have distinct but teleologically complementary scopes of applicability within these powers. Consequently, we will explore how the role of the administrative mediator can represent a new administrative employment opportunity resulting from these new technological advancements, in search of the empathy and humanity compromised by the purely objective and amoral actions of any form of artificial intelligence.